Neuroprotective effects of Ocimum basilicum extract against hydrogen peroxide-induced oxidative stress in SK-N-SH neuroblastoma cells - Manali Haniti Mohd-Zahid; Juriyati Jalil; Chan, Kok Meng; Norazrina Azmi (Penerbit Universiti Kebangsaan Malaysia, 2018)
Neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease are characterized by the progressive loss of neurons. One of the contributing factors for these diseases is oxidative stress, characterized by the imbalance of free radicals production and antioxidant defense mechanisms. In the present study, the neuroprotective effects of Ocimum basilicum var. thyrsiflora against hydrogen peroxide (H2O2)-induced oxidative stress in SK-N-SH neuroblastoma cells were evaluated. The exposure of SK-N-SH cells to 50 μM H2O2 for 24 h induced cytotoxicity and apoptosis as measured by cell viability and flow cytometry, respectively. Pretreatment with ethyl acetate (ObEA) fraction at 3.1-25 μg/mL showed the highest protection against H2O2-induced cell death compared to other fractions and crude extract by increasing cell viability and reducing apoptosis. The evaluation of antioxidant capacity via 1, 1-diphenyl-2-picrylahydrazyl (DPPH) and ferric reducing/antioxidant power (FRAP) assays showed ObEA possessed the highest antioxidative properties. The intracellular reactive oxygen species (ROS) production of H2O2 in untreated cells increased by 2.39-fold compared to the control and was significantly attenuated by the 2 h pre-treatment of O. basilicum (p<0.05). The reduction in intracellular superoxide dismutase (SOD) induced by H2O2 was also abrogated by the pretreatment of O. basilicum. These findings suggested that O. basilicum is potentially neuroprotective against oxidative damage in neuronal cells by scavenging free radicals, restoring SOD activities and eventually prevent cell death.